Pesantren dan Perubahan Sosial - Hartanto, Rudy; Priyanto, Catur; Mustamik, Khoirul (Lembaga Yasin AlSys, 2025)
Pesantren is an Islamic educational institution led by a kiai, operating through both formal and non-formal pathways, with the goal of studying, understanding, internalizing, and practicing Islamic teachings derived from classical texts. It emphasizes moral development and character building as a guide for daily life, along with a spirit of devotion in seeking divine (ilāhiyyah) values. Pesantren maintains a high level of integration with the surrounding community. Its function extends beyond education, serving as a social institution, a center for religious dissemination, and a moral reference for society. As an agent of socio-cultural change, pesantren plays a role in three key areas: 1) Tafaqquh fi al-din – Deepening religious knowledge through educational and dakwah institutions. 2) Teaching classical Islamic texts (kitab kuning) – Using a dialogical, critical, and open approach, without dogmatic enforcement of specific doctrines or opinions. 3) Instilling akhlak al-karimah – Cultivating noble character both within and beyond the pesantren environment.